The Association of Aortic Stenosis Severity and Symptom Status With Morbidity and Mortality - Matthew D. Solomon, MD, PhD; Alan S. Go, MD; Thomas Leong, MPH; Elisha Garcia, BS; Kathy Le, MPH; Femi Philip, MD; Edward McNulty, MD; Jacob Mishell, MD; Andrew N. Rassi, MD; David C. Lange, MD; Catherine Lee, PhD; Anthony DeMaria, MD; et al. (JACC: Advances)
Background: The relationship between aortic stenosis (AS) severity, AS-related symptoms, and clinical outcomes is poorly understood. Objectives: The purpose of this study was to evaluate whether potential AS-related symptoms at diagnosis are associated with outcomes, including death and AS-related hospitalization. Methods: In this retrospective cohort study from a large, integrated health care system serving >4.5 M individuals, we applied validated natural language processing algorithms to echocardiogram reports to identify physician-assessed AS severity and potential AS-related symptoms (eg, chest pain, syncope, dyspnea, worsening heart failure) via diagnosis codes and natural language processing-applied physician notes. Of 602,821 adults with echocardiograms from 2010 to 2019, we identified 40,333 adults diagnosed with AS and applied Cox models to examine associations between AS-related symptoms, AS severity, and clinical outcomes over a median follow-up of 2.2 years. Results: Most patients with AS had potential AS-related symptoms (mild: 80%, mild-moderate: 77%, moderate: 77%, moderate-severe: 85%, severe: 87%). Symptomatic patients were older (mean age 78 vs 75 years; P < 0.01), more often female (51% vs 47%; P < 0.01), and had greater comorbidity burden. After multivariable adjustment, symptom status strongly predicted risk. Patients with symptomatic moderate AS had a similar risk to those with severe AS without symptoms (adjusted HR: 1.77 [95% CI: 1.65-1.91] vs 1.81 [95% CI: 1.51-2.17] for death, P = 0.81; aHR: 2.27 [95% CI: 2.13-2.41] vs 2.40 [95% CI: 2.08-2.77] for AS-related hospitalization, P = 0.42). Conclusions: These findings suggest that symptom status, independent of AS severity, is a key risk factor for adverse outcomes. Further research is needed to assess the benefits of early intervention in these high-risk groups.